PSYCHOLOGICAL EFFECTS OF CONSUMPTIVE BEHAVIOR ON PSYCHOLOGY STUDENTS - Yoga Aji Nugraha; Kiki Nurastriani; Orina Yuliandira; Belly Lestari; Jimi Mardiansyah (Journal of Psychology and Social Sciences, 2023)
The purpose of this research is to find out what is the influence of psychological conditions on the consumptive behavior of psychology students at Islamic University of Raden Fatah Palembang class of 2020-2021. The method used in this study uses a quantitative approach, which places more emphasis on numerical data analysis or numbers that will be processed using statistical analysis methods of normality tests and simple regression. The type of research used in this study is a type of survey. Respondents produced in this survey amounted to 46 respondents who were determined using a purposive sampling technique. As for the method used in collecting data using online surveys via Google forms with a scale likert. There are two forms of questions that use Likert, namely positive questions to measure positive interest, and negative questions to measure negative interest. Positive questions were given a score of 4, 3, 2, and 1 while negative questions were given a score of 1, 2, 3, and 4. Form of Likert scale answers consist of strongly agree, agree, disagree, disagree, and strongly disagree. The results of the validity test on the consumptive behavior instrument show that there are 13 questions overall. The valid validity test results are 46 and the normality test results of ANOVA are 0.39% and the coefficients are 706%.